Numerical modelling and experimental validation of crater formation in WEDM hybrid turning of Ti-6Al-4V alloy. (April 2021) - Vignesh, M; Ramanujam, R
Wire electrical discharge hybrid turning (WEDHT) is one of the unconventional machining process following thermo-electric material removal principle to machine cylindrical components at meso and micro scale with very high accuracy and precision. Thermal simulation and validation of Ti6Al4V alloy on temperature profile, crater formation, rate of material removal during WEDHT process was reported less by previous researchers and this creates path for framing the objective. The objective of the present study is to, numerically simulate and validate the material removal through crater formation and temperature generation in WEDHT process using COMSOL Multiphysics 5.2. The time-dependent and heat transfer in solid module is chosen with current, voltage and discharge ON time (TON ) of 106, 109, 112 µs as the input parameters for modelling. With the same varying TON, varying wire feed rate of 3, 4, 5 m/min and varying servo feed of 5, 7, 9 mm/min, the validation experiments are performed to validate the crater formed. Based on the comparison plot, the numerically predicted and experimentally obtained data resulted in the error percentage of 41.6%, 21.2%, 15% for 106, 109 and 112 µs discharge ON time, respectively. The images of the crater formed on the work material are captured using scanning electron microscope and atomic force microscopy images. The results of the numerical and experimental study, proved that, high the TON, more would be material removal.